Estimasi Prevalensi Kecelakaan Lalu Lintas dengan Metode Capture-Recapture - Sayekti Udi Utama, Rahadyan Magetsari, Vitalis Pribadi (Berita Kedokteran Masyarakat (BKM), 2008)
Background: Accident is a global health problem. In 2002 the major cause of accident leading to death is road accident (22.8%). In 2003–2005 the number of road accidents in the Province of Yogyakarta Special Territory is decreasing; however the fatality and ratio of road accident and the number of victims are increasing. In Indonesia there are two kinds of reporting made whenever there is a road accident. When the accident is handled by the police, data are kept at the police office and hospital; however, when it is not handled by the police, data are kept only at the hospital, not at the police office. In the Province of Yogyakarta Special Territory data of road accident are based on the report of Traffic Office of Yogyakarta Special Territory Regional Police so that they may not reflect the actual road accidents.Objective: To estimate the prevalence of road accidents by combining data sources from both the police and hospital at the Province of Yogyakarta Special Territory 2006.Method: This was a descriptive study with survey design. It was carried out at the Province of Yogyakarta Special Territory from May to August 2007. Analysis was made using capture-recapture method. Data entry and calculation were carried out using web-based computer program with Personal Home Page language programming and the database was maintained in MySQL.Result: There were as many as 1,721 data from 5 district police office/big city police office and 5,422 data from 22 hospitals and there were as many as 751 similar data. Data from the police office were 100% complete and from hospitals were not as complete as those from the police office. Coverage of data from the police office was 13.9% and from hospitals was 43,7%. The result of the study showed that the prevalence of road accident based on data from the police office was 51 per 100,000 people and from the hospital was 161 per 100,000 people; whereas the prevalence of the result of estimation using capture-recapture method was 369 per 100,000 people (12,417 cases – 95% CI:11.799-13.035) with highest prevalence for male of 16–25 years old, living and having road accidents at Sleman District.Conclusion: The estimation of the prevalence of road accident using capture-recapture method at the Province of Yogyakarta Special Territory in 2006 was 369 per 100,000 people, 2.28 times greater than data of hospitals and 7.2 times greater than data of the police office with under reporting as much as 724% at the police office and 229% at hospitals.Keywords: road accident, capture-recapture method, prevalence